Multifunctional properties of soy milk fermented by enterococcus faecium strains isolated from raw soy milk - Martínez Villaluenga, Cristina (2012)
Lactic acid bacteria (LAB) isolated from soy milk were used to produce a multifunctional fermented food. Seven isolates were screened for their ability to produce peptides and free isoflavones in soy milk. The antihypertensive, antioxidant, and anti-inflammatory properties of the resulting fermented soy milks were evaluated in vitro using biochemical assays. Isolates 1-5 were found to be producers of fermented soy milk with angiotensin I converting enzyme inhibitory activity (ACEI). Isolate 3 was found to be a producer of free isoflavones that increased the antioxidant and anti-inflammatory potential of fermented soy milk. LAB isolates 2-5 were submitted to genetic profiling and a characterization scheme. These isolates were identified as Enterococcus faecium, and none of them contained virulence determinants or resistance to antibiotics. In conclusion, this study shows that the application of E. faecium isolate 3 for multifunctional food production from soy milk could be a promising strategy in the prevention therapy against cardiovascular disease.